The Effect of Job Stress and Motivation on Employee Performance through Job Satisfaction as an Intervening Variable in Lakeview Hotels & Restaurants in Kintamani Tourism Village - Ni Wayan Eka Putri; Ni Wayan Sitiari; I. B Agung Dharmanegara; D A Gladysia Sistadanta KDS (Global Researcher Network, 2022)
This research aims to analysis the effect of job stress and motivation on employee performance through job satisfaction as an intervening variable in lakeview hotels & restaurants in Kintamani tourism village. This research was conducted at LakeView Hotel & Restaurant in the Tourism Village of Kintamani. Employee performance is a very important thing in the company's efforts to achieve its goals. Creating good employee performance is not easy because employee performance can be created if the variables that can influence it can be well accommodated and accepted by all employees in an organization or company. In this study employee performance is influenced by job satisfaction, job stress and motivation work. Respondents of this study were 79 LakeView Hotel & Restaurant employees in the Tourism Village of Kintamani. Data analysis was performed using PLS (partial least square). The results of the analysis of this study indicate that: (1) job stress has a negative and significant effect on employee performance, (2) work stress has a negative and significant effect on job satisfaction, (3) work motivation has a positive and significant effect on job satisfaction, ( 4) work motivation has a positive and significant effect on employee performance, (5) job satisfaction has a positive and significant effect on employee performance.